2021
DOI: 10.1186/s40691-020-00228-3
|View full text |Cite
|
Sign up to set email alerts
|

I wear, therefore I am: investigating sneakerhead culture, social identity, and brand preference among men

Abstract: While the popularity of athletic footwear or “sneakers” has been widely assessed within academic literature, few studies to date have examined the influence of a specific sneaker subculture called “Sneakerheads”. Moreover, the brand preferences and brand identities that may exist within the Sneakerhead subculture have not been extensively examined. To address this gap in the research, semi-structured interviews were conducted with 12 male, self-identified Sneakerheads. The main goal of the research was to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Finally, the variables that impact the behavior of sneakerhead subculture have not been fully observed in the academic context. The authors found only two other studies that have examined this subculture, using qualitative methodology and reporting themes (Choi & Kim, 2019;Matthews et al, 2021);…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…Finally, the variables that impact the behavior of sneakerhead subculture have not been fully observed in the academic context. The authors found only two other studies that have examined this subculture, using qualitative methodology and reporting themes (Choi & Kim, 2019;Matthews et al, 2021);…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…However, the passionate consumption of young people has given rise to some irrational factors in the sneaker culture, where sneakers have come to symbolize their own identities. Furthermore, the emergence of blind consumption is a new trend created by advertising and the media [ 26 ]. Many individuals have criticized the consumerism associated with the sneaker culture, and the rapid expansion of this culture has encouraged symbolic consumption from the outset.…”
Section: Sneaker Consumption Culture Based On Bd Analysismentioning
confidence: 99%
“…An example is Sneakerheads who exhibit a clear sense of group identity related to motivation, behavior, and brand identity within the Sneakerhead community. Sneakerheads also define Sneakerhead lifestyles and explain their unique behaviors and practices within the culture Matthews et al, 2021).…”
Section: Introductionmentioning
confidence: 99%